Context characteristics and their effects on students’ situational interest in chemistry - Habig, Sebastian; Blankenburg, Janet; Van Vorst, Helena; Fechner, Sabine; Parchmann, Ilka; Sumfleth, Elke (International journal of science education, 2018)
Many studies in science education acknowledge the positive effects of context-based learning on students’ interest and attitudes. However, little is known about the design criteria of contextual situations generating these effects and how facets of students’ situational interest are affected while learning in a contextualised setting. This paper ties in with this initial situation and reports results of two projects analysing the influence of context characteristics on students’ situational interest, referring to contexts as task parameters in the first project and as learning activities in the second. In the first project, everyday related and unique contexts are compared, and the effects of different contextual topics on student learning are investigated. Particularly, regarding the feeling- and value-related valence of situational interest, the results of different studies will be compared and interpreted. The second project investigated structures of interest related to activities along an adapted version of the ‘RIASEC’-model for different content areas and age groups. The chosen contents were embedded in personal as well as societal and professional context settings. Finally, we summarise the relevance of the different models, results and instruments to better understand different notions of interest and outline implications for further studies about teaching that improves student learning.
Created from Fastlane, Scopus look-up
Keywords: Context characteristics; interest; RIASEC + N; situational interest